Management of impacted maxillary central incisor in mixed dentition - Anson, Ma. Criselda M. (The Journal of the Philippine Dental Association)
Management of impacted central incisor may be incorporated into a mere comprehensive treatment procedure to include achieving a Class I molar relationship, prevention of arch length deficiency, and alignment of incisor into an ideal overbite and overjet relationship.